Implementasi PjBL Kurikulum Merdeka untuk Meningkatkan Kolaborasi Siswa dalam Pembelajaran IPAS Kelas IV (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the application of the Project-Based Learning (PjBL) model in IPAS learning on economic activities and to examine its effect on the collaboration skills of fourth-grade students at Saraswati 1 Elementary School in Denpasar. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of PjBL through six stages of implementation significantly enhances collaborative aspects such as role distribution, open communication, cooperation, and shared responsibility. Teachers and students responded positively to this method, as learning became more meaningful and enjoyable. The projects created by students reflected active engagement and solid teamwork. In conclusion, the PjBL model is effective in enhancing students' collaboration skills and is relevant for implementation within the context of the Merdeka Curriculum to support the strengthening of the Pancasila learner profile.